NU Online’s Value-Based Health Rhetoric to Build Muslim Community Resilience - Nia Ashton Destrity; Nilam Wardasari; Fariza Yuniar Rakhmawati (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2026)
This study aims to explore the rhetoric of value-based health messages on the Indonesian Islamic organization Nahdlatul Ulama (NU) website, NU Online, that is used to build community resilience. Based on a rhetorical analysis of 71 articles from 2024 to 2025, the research indicates that NU integrates rational, emotional, and Islamic spiritual-religious approaches. The rhetoric emphasizes the elements of act (Islamic behavior and therapy), agency (Islamic activities and worship), and agent (authority figures and Islamic figures such as the Prophet Muhammad and Muslim scholars). Solutions to health problems are based on Islamic values ​​grounded in morality (akhlaq) and etiquette (adab).